Economic analysis of the project of warehouse centralization in the paper production company - Stević, Željko; Mulalić, Enis; Božičković, Zdravko; Vesković, Slavko; Đalić, Irena (Serbian Journal of Management, 2018)
In the modern conditions, business requires constant rationalization of all activities and processes that occur in the logistics system. One of the preconditions for ensuring the competitiveness in the market is to manage the own performance. This paper presents research that relates to the project of centralization of the warehouse in the company of paper production. Currently, any production facility has its own warehouse that is, through executed decomposition, proved like a poor solution. Any project requires certain investment funds, which are in this case over half million EUR, because it is a large and complex logistics company that employs about one thousand workers. The focus of this paper is an economic analysis of the project of centralization of warehouse. The new centralized system gives better results in the comparison with the current system of decentralization. Considering the savings, which are realized by switching to a centralized warehouse system, and required investment funds, repayment period of the same is slightly less than five years, what is relatively a short period.